Childhood-onset systemic lupus erythematosus (cSLE) and malignancy: a nationwide multicentre series review - Brufatto, Matheus Zanata [UNESP]; Lanças, Sean Hideo Shirata [UNESP]; de Albuquerque Pedrosa Fernandes, Taciana [UNESP]; Sallum, Adriana Maluf Elias; Campos, Lucia Maria Arruda; Sakamoto, Ana Paula; Terreri, Maria Teresa; Sztajnbok, Flavio Roberto; Bica, Blanca Elena Rios Gomes; Ferriani, Virginia Paes Leme; de Carvalho, Luciana Martins; Silva, Clovis Artur Almeida; et al. (Springer Nature, 2024)
Background: Increased malignancy frequency is well documented in adult-systemic lupus erythematosus (SLE), but with limited reports in childhood-onset SLE (cSLE) series. We explored the frequency of malignancy associated with cSLE, describing clinical and demographic characteristics, disease activity and cumulative damage, by the time of malignancy diagnosis. Method: A retrospective case-notes review, in a nationwide cohort from 27 Pediatric Rheumatology centres, with descriptive biopsy-proven malignancy, disease activity/damage accrual, and immunosuppressive treatment were compiled in each participating centre, using a standard protocol. Results: Of the 1757 cSLE cases in the updated cohort, 12 (0.7%) developed malignancy with median time 10 years after cSLE diagnosis. There were 91% females, median age at cSLE diagnosis 12 years, median age at malignancy diagnosis 23 years. Of all diagnosed malignancies, 11 were single-site, and a single case with concomitant multiple sites; four had haematological (0.22%) and 8 solid malignancy (0.45%). Median (min–max) SLEDAI-2 K scores were 9 (0–38), median (min–max) SLICC/ACR-DI (SDI) score were 1 (1–5) Histopathology defined 1 Hodgkin's lymphoma, 2 non-Hodgkin's lymphoma, 1 acute lymphoblastic leukaemia; 4 gastrointestinal carcinoma, 1 squamous cell carcinoma of the tongue and 1 anal carcinoma; 1 had sigmoid adenocarcinoma and 1 stomach carcinoid; 3 had genital malignancy, being 1 vulvae, 1 cervix and 1 vulvae and cervix carcinomas; 1 had central nervous system oligodendroglioma; and 1 testicle germ cell teratoma. Conclusion: Estimated malignancy frequency of 0.7% was reported during cSLE follow up in a multicentric series. Median disease activity and cumulative damage scores, by the time of malignancy diagnoses, were high; considering that reported in adult series.
Keywords: Childhood-onset systemic lupus erithematosus; Leukaemia; Lymphoma; Malignancy; Registry; Solid malignancy